From Beethoven Performance to Beethoven Interpretation: Carl Czerny and Franz Liszt’s Evolving Relationship, 1822–57 - Köhnken, Camilla (Leuven Leuven University Press, 2024)
The essay examines the relationship between Carl Czerny and Franz Liszt beyond the teacher-student period of 1822–23. It traces the lifelong friendship between the two artists and their shared activities in building the Beethoven myth. Czerny’s additions in his early piano versions of Beethoven’s violin sonata op. 47 "Kreutzer" suggest that Liszt might have adopted and incorporated Czernyian teachings still rooted in 18th century performance practice in his Beethoven performances (often criticized as too free or wayward) rather than merely indulging in personal romantic exuberance.
FRIS
1
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850